A Reconfigurable S-/X-Band GaN MMIC Power Amplifier - Kang, Li; Chen, Wenhua; Wu, Aimin (IEEE microwave and wireless components letters, 2022)
A reconfigurable S -/ X -band monolithic microwave integrated circuit (MMIC) power amplifier (PA) utilizing a 0.25- μ \text{m} GaN HEMT technology is presented in this letter. A dual-frequency output matching network combined with reconfigurable interstage and input matching networks are adopted to realize the band configuration function of the PA. Moreover, the control terminals of all the on-chip switches are properly consolidated to simplify the demanded control signal. The MMIC can be easily configured for 2-3 GHz S -band and 10-12 GHz X -band. When configured for S -band, the MMIC achieves 22 dB of gain, an input return loss (IRL) better than −10 dB, more than 30.5 dBm of saturated output power, and a PAE of 15%-24%. When configured for X -band, the MMIC achieves 14 dB of gain, an IRL better than −15 dB, more than 31 dBm of saturated output power, and a PAE of 18%-22%.